ChK1 activation induces reactive astrogliosis through CIP2A/PP2A/STAT3 pathway in Alzheimer's disease. Issue 3 (23rd February 2022) - Zhou, Ying; Liu, Xiaoyuan; Ma, Shuqing; Zhang, Nan; Yang, Dichen; Wang, Ling; Ye, Simin; Zhang, Qiongying; Ruan, Jing; Ma, Jun; Wang, Shiyi; Jiang, Nan; et al.
Abstract: Cancerous Inhibitor of PP2A (CIP2A), an endogenous PP2A inhibitor, is upregulated and causes reactive astrogliosis, synaptic degeneration, and cognitive deficits in Alzheimer's disease (AD). However, the mechanism underlying the increased CIP2A expression in AD brains remains unclear. We here demonstrated that the DNA damage‐related Checkpoint kinase 1 (ChK1) is activated in AD human brains and 3xTg‐AD mice. ChK1‐mediated CIP2A overexpression drives inhibition of PP2A and activates STAT3, then leads to reactive astrogliosis and neurodegeneration in vitro. Infection of mouse brain with GFAP‐ChK1‐AAV induced AD‐like cognitive deficits and exacerbated AD pathologies in vivo. In conclusion, we showed that ChK1 activation induces reactive astrogliosis, degeneration of neurons, and exacerbation of AD through the CIP2A‐PP2A‐STAT3 pathway, and inhibiting ChK1 may be a potential therapeutic approach for AD treatment.